2018
DOI: 10.1111/exd.13789
|View full text |Cite
|
Sign up to set email alerts
|

Hypotonic stress response of human keratinocytes involves LRRC8A as component of volume‐regulated anion channels

Abstract: The barrier function of the human epidermis is constantly challenged by environmental osmotic fluctuations. Hypotonic stress triggers cell swelling, which is counteracted by a compensatory mechanism called regulatory volume decrease (RVD) involving volume‐regulated anion channels (VRACs). Recently, it was discovered that VRACs are composed of LRRC8 heteromers and that LRRC8A functions as the essential VRAC subunit in various mammalian cell types; however, the molecular identity of VRACs in the human epidermis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
(128 reference statements)
0
14
0
Order By: Relevance
“…However, the genes encoding the channels remained elusive and highly controversial until 2014 when two independent groups definitively identified the Leucine‐Rich Repeat Containing 8A‐E (LRRC8A‐E) genes that encode VRACs (Kumar et al, ; Voss et al, ) Results from gene disruption, heterologous expression, and cryo‐EM experiments indicate that VRACs are likely hexameric channels that contain LRRC8A and at least one other LRRC8 subunit (i.e., LRRC8B, LRRC8C, LRRC8D, or LRRC8E) (Strange et al, ). Importantly for the present study, several groups have shown that genetic disruption of the LRRC8A gene abolishes VRAC activity in a variety of different cell types (Bao et al, ; Platt et al, ; Stuhlmann, Planells‐Cases, & Jentsch, ; Trothe et al, ).…”
Section: Introductionmentioning
confidence: 54%
“…However, the genes encoding the channels remained elusive and highly controversial until 2014 when two independent groups definitively identified the Leucine‐Rich Repeat Containing 8A‐E (LRRC8A‐E) genes that encode VRACs (Kumar et al, ; Voss et al, ) Results from gene disruption, heterologous expression, and cryo‐EM experiments indicate that VRACs are likely hexameric channels that contain LRRC8A and at least one other LRRC8 subunit (i.e., LRRC8B, LRRC8C, LRRC8D, or LRRC8E) (Strange et al, ). Importantly for the present study, several groups have shown that genetic disruption of the LRRC8A gene abolishes VRAC activity in a variety of different cell types (Bao et al, ; Platt et al, ; Stuhlmann, Planells‐Cases, & Jentsch, ; Trothe et al, ).…”
Section: Introductionmentioning
confidence: 54%
“…LRRC8A-KO cells were prepared using CRISPR/Cas9 tools, as has been described [ 53 ]; however, plasmids were used for expression cassette delivery. Cells were transfected with plasmids (2 µg) using Lipofectamin 2000 according to the manufacturer’s instructions and potentially edited cells selected via Blasticidin treatment (Fisher Scientific GmbH, Schwerte, Germany, 2 µg/µL) for 9 d [ 53 ]. For primer sequences, see Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Since the molecular structure of VRAC was identified, a series of antibodies against different regions of the basic subunits of the family LRRC8 have been developed and effectively used [4,5,9,14,17,18,[23][24][25][26]. Before now, VRAC subunit proteins were detected mostly by immunoblotting of the solubilized whole cells [27][28][29][30][31][32], less often of cell membranes lysates [14,33,34] or by imaging cells that have been permeabilized for staining [35,36]. Furthermore, these data were mostly obtained from cells specifically rich in VRAC such as epithelial cells, astrocytes, vascular smooth muscle cells and transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Surface localization of LRRC8A has been shown in several cases [4,[36][37][38]. Intracellular and plasma membrane localization of GFP-tagged LRRC8A was visualized in living KCP-4 and KB cell lines by immunoimaging [30].…”
Section: Discussionmentioning
confidence: 99%